CNN and LSTM-Based Multimodal Data Fusion for Performance Optimization in Aerobics Using Wearable Sensors - Tan, Danhua (Informatica, 2025)
Aerobics is a high-intensity, multi-dimensional sport. Its motion evaluation places higher demands on data quality and time series modeling capabilities. This paper proposes a method for evaluating aerobics motion that integrates wearable sensors and motion tracking systems. It combines convolutional neural networks (CNNs) with long short-term memory networks (LSTMs) to perform fusion analysis on multimodal data from accelerometers, gyroscopes, magnetometers, and Kinect motion capture systems. To improve data quality, Kalman filtering, time synchronization, and wavelet transform techniques are introduced to preprocess the raw data. Experimental results show that this method performs well in motion classification tasks: in indoor low-intensity training scenarios, the accuracy of the CNN model increases from 74.5% to 87.1%; in high-intensity training scenarios, the accuracy increases from 75.0% to 88.2%. After combining with LSTM, the model further enhances the modeling capabilities of motion time series features and improves the recognition accuracy of complex motions. In different training scenarios, the average improvement rate of motion scores is 25.8%. The system feedback delay is controlled within 200 milliseconds, with good real-time and practical performance. This method provides aerobics athletes with high-precision movement assessment and personalized training suggestions, promoting the intelligent and personalized development of sports training.